Упростите выражения (34.13-34.14): 34.13. 1) 2а3+9 – 2(a + 1)(а? — а+ 1);
2) х(х + 2)(х-2) - (х-3)(х2 + 3x +9);
3) 3(b - 1)2 + (b + 2)(b2 - 2b + 4) - (b+ 1) 3;
4) (а-1) 3 - 4a(a + 1)(a - 1) + 3(а-1)(а? +а+ 1).
34.14. 1) (x+2)(х2 - 2х + 4) - х(х - 3)(х + 3) - 42;
2) (x-3)(х2 + 3x +9) - х(х2 - 16) + 21;
3) (2x-1)(4х2 + 2х + 1) - 23 - 4x(2х2 + 3);
4) 16x(4х2 - 5) + 17 - (4х + 1)(16х2 - 4х + 1).
Доказать , что функция f(x)=(x+4)|x-5|+(x-4)|x+5| является нечётной.
* * * f(-5) = -10 ; f(5) =10 ; f(0) =4*5 - 4*5 = 0. * * *
a) x ≥ 5 .
f(x) = (x+4)*(x -5) + (x - 4)*(x +5) = 2(x² - 20) .
---
b) x ≤ - 5 .
f(x) = (x+4)*(-(x-5)) + (x- 4)*(-(x+5) ) = - ( (x+4)*(x-5) +(x - 4)*(x+5) ) =
= - 2(x² -20) .
f(-x₁) = - f(x₁) , т.к. если x₁ ≤ - 5 ⇒ - x₁ ≥ 5 .
---
c) - 5 < x < 5
f(x) = (x+4)*(- (x-5) ) + (x - 4)*(x +5) = - (x+4)*(x - 5) + (x - 4)*(x +5) =
= 2x .
Значит , если - 5 < x₀ ≤ 0 ,то 0 ≤ - x₀ < 5
f(- x₀) =-2x₀ = - 2f(x₀) .
функция f(x)=(x+4)|x-5|+(x-4)|x+5| является нечётной.
-2(x² -20) 2x 2x 2(x² -20)
[-5] [0] [5]
* * * * * * *P.S.* * * * * * *
f(-5) = -2((-5)² -20) =10 или f(-5) =2*(-5) = - 10 .
f(5) =2(5² -20) =10 или f(5) =2*5 =10.
f(0) =2*0 =2*(-0) =0 .